TANGGUNGJAWAB NEGARA TERHADAP KEBAKARAN HUTAN DAN LAHAN DALAM PERSPEKTIF HUKUM NASIONAL DAN ISLAM - Syafi’ul Anam; Muhammad Afdhal Askar (JURIS (Jurnal Ilmiah Syariah), 2020)
The responsibility given by the state to the occurrence of forest and land fires so far has not been considered optimal. Whereas the state has responsibilities towards its citizens, one of which is in ensuring the rights of citizens to get a clean and healthy environment. The liability referred to arises from the legal relations between the countries as mentioned in the fourth alinia of the Preamble of the 1945 Constitution through the phrase "protecting the entire Indonesian nation and the whole of Indonesian blood". Whereas in the Islamic perspective it also regulates that the purpose of the state is to create benefit for its citizens. Therefore, various losses to citizens due to forest and land fires should have been the responsibility of the state. So that what is demanded from the role of the State is not only prevention but also overcoming various impacts of losses caused as a result. Research is a normative juridical study using secondary data as the main. The nature of this research is qualitative.